Lidar engineering introduction to basic principles - Gimmestad, Gary G.; Roberts, David W. 1961- (Cambridge University Press, 2023)
Explore the spectrum of lidar engineering in this one-of-a-kind introduction. For the first time, this multidisciplinary resource covers all the scientific and engineering aspects of atmospheric lidar - including atmospheric science, spectroscopy, lasers and eye safety, classical optics and electro-optics, electrical and mechanical engineering, and software algorithms - in a single comprehensive and authoritative book. Discover up-to-date material not included in any other book, including simple treatments of the lidar crossover range and depolarization in lidar signals, an improved explanation of lidar data inversion algorithms, digital signal processing applications in lidar, and statistical limitations of lidar signal-to-noise ratios. This is an ideal standalone text for students seeking a thorough grounding in lidar, whether through a taught course or self-study